1988
DOI: 10.1007/bf01044907
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weather on mood, productivity, and frequency of emotional crisis in a temperate continental climate

Abstract: A group of 62 mostly university student subjects kept structured diaries of their feelings and their productivity for six weeks in Illinois in early autumn. During the same period, daily frequency of telephone calls to a crisis intervention service in the same community was monitored, and complete daily weather data for the vicinity were provided by a local meteorological research facility. Major findings are as follows. The weather appears to influence mood and productivity, but only to a small extent compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 15 publications
3
17
1
1
Order By: Relevance
“…The researchers strained to draw a final conclusion, however, and determined in the end that “people differ in their sensitivity to daily weather changes” (Denissen et al 2008, p. 667). This seems to corroborate the findings reported by Barnston (1988), who argued that psychologically troubled people are generally more susceptible to fluctuations in mood stemming from weather conditions than others. Also, the weather’s impact on people’s mood may vary by season.…”
Section: Theoretical Considerationssupporting
confidence: 91%
“…The researchers strained to draw a final conclusion, however, and determined in the end that “people differ in their sensitivity to daily weather changes” (Denissen et al 2008, p. 667). This seems to corroborate the findings reported by Barnston (1988), who argued that psychologically troubled people are generally more susceptible to fluctuations in mood stemming from weather conditions than others. Also, the weather’s impact on people’s mood may vary by season.…”
Section: Theoretical Considerationssupporting
confidence: 91%
“…Hribersek et al (1987) researched 21-months of the calls to a telephone counseling service at Louvain. Contrary to Barnston (1988) they found that women are more sensitive to weather compared to men, which they explained with hormonal differences. They also explained the phenomenon women make more calls when the weather is adverse with the fact they prefer to stay at home during severe weather.…”
Section: Introductioncontrasting
confidence: 40%
“…Most of them focus on the relationship between the weather and mood. Barnston (1988) performed an experiment in which 62 university student subjects in Illinois kept structured diaries of their feelings and their productivity for six weeks in early autumn. During the same period, he monitored the daily frequency of telephone calls to a crisis intervention service and collected the complete daily weather data for the vicinity from a local meteorological research facility.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of weather on human emotion and social interactions is well supported in the literature. It has been shown that weather has both seasonal and daily effects on mood; it is associated with productivity levels, emotional crises, hostility, memory, and cognition (Denissen, Butalid, Penke, & van Aken, 2008;Persinger, 1975;Barnston, 1986;Dubitsky, Weber, & Rotton, 1993;Keller, et al, 2005).…”
Section: Does Weather Actually Affect Tipping? An Empirical Analysis mentioning
confidence: 99%